Mental Workload Assessment Using NASA TLX and DRAWS Methods: Penilaian Beban Kerja Mental Menggunakan Metode NASA TLX dan DRAWS - Winandri, Nadya Chaerunisa; Putra, Boy Isma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Mental workload is a critical factor affecting worker performance, fatigue, and decision-making in industrial environments. Specific Background Various methods such as NASA-TLX and Defence Research Agency Workload Scale (DRAWS) are widely used to measure mental workload in different work settings. Knowledge Gap However, limited studies compare and apply these methods simultaneously to evaluate workload conditions in specific operational contexts. Aims This study aims to analyze and measure mental workload using NASA-TLX and DRAWS methods to identify dominant workload factors. Results The results indicate that several workload indicators contribute significantly to high mental workload levels, particularly related to task demand and time pressure. The analysis shows variations in workload across different job activities. Novelty This study applies a comparative measurement approach using two established workload assessment methods within a single analysis framework. Implications The findings provide practical insights for workload management, task allocation, and improving worker performance in industrial systems. Keywords: Mental Workload, NASA TLX, DRAWS, Workload Analysis, Ergonomics Key Findings Highlights Workload levels vary across different job tasks Task demand and time pressure identified as dominant factors Dual-method assessment provides comprehensive evaluation